Variability of the West Kamchatka Current in winters of 1994–2019, by altimetry data - V. V. Kolomeytsev (Известия ТИНРО)
Averaged schemes of the geostrophic circulation on surface of the eastern Okhotsk Sea in winter months are plotted using the data of satellite altimetry measurements. Variations of the surface water transport by the West Kamchatka Current through the latitude of 54о N, between 153о E and the coast of Kamchatka, are analyzed. The current was strengthened in the winters of 1996, 1997, 2009, 2010, and 2013; it was relatively weak in the winters of 2002, and 2007. Statistical dependences of the sea surface temperature and ice cover on the West-Kamchatka Current intensity are calculated for entire winter season and by months; they are statistically significant for all winter months. The West Kamchatka Current variation determines up to 33–36 % of these indices variability.